2010
DOI: 10.1007/s10433-010-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Day care centre attendance and quality of life in depressed older adults living in the community

Abstract: Late-life depression is associated with disabled functioning and a poor quality of life (QOL). The aim of this cross-sectional study was to find out whether the attendance of a day care centre (DC) was associated with QOL in community-dwelling older adults suffering from a depressive disorder without dementia. The study enrolled 149 depressed older adults aged 70 or older, who consecutively underwent a comprehensive geriatric assessment from April to July 2008 at the Geriatric Medicine Unit of the Fondazione O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…This can be because quality of life is mostly influenced by self-assessments of health and economic status; thus the frequency and duration of use of day care centres have no effect on the quality of life of its users. However, this is in contrast to findings from a recent Italian study (Bilotta et al 2010) that greater weekly attendance at day care centres was related to a better quality of life among older patients suffering from depression. One possible explanation for these findings is that because the day care centres in Israel operate according to the social model, they do not provide health and rehabilitation services.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This can be because quality of life is mostly influenced by self-assessments of health and economic status; thus the frequency and duration of use of day care centres have no effect on the quality of life of its users. However, this is in contrast to findings from a recent Italian study (Bilotta et al 2010) that greater weekly attendance at day care centres was related to a better quality of life among older patients suffering from depression. One possible explanation for these findings is that because the day care centres in Israel operate according to the social model, they do not provide health and rehabilitation services.…”
Section: Discussioncontrasting
confidence: 99%
“…This type of service is aimed to sustain and preserve the functioning of frail older people, allowing them to age in place and meet some of their long-term care needs (Anetzberger 2002; Krout 1995). It is believed that attendance at adult day care centres can promote older adults' quality of life (Bilotta et al 2010). Quality of life among older people has become a major focus for research and a driver of social policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of our study point to the need of a timely diagnosis and an effective treatment of depression in older people living alone in order to improve their QOL. In older people suffering from depression without cognitive impairment it has been recently demonstrated that a higher weekly attendance of a generic daily care centre, where social participation and companionship are usually promoted alongside the provision of physical exercise and educational therapy, is associated with a better QOL independent of living conditions, functional status and severity of depression (Bilotta et al. 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the articles seem to be immediate responses to the points that we concluded need more attention: they are from authors in South Europe (Bilotta et al 2010;Sousa et al 2010). One of these is based on qualitative methods and is moreover innovative in that it addresses a common issue of life which has received very little attention from researchers so far: the inheritance process (Sousa et al 2010).…”
mentioning
confidence: 96%